Importance of rainfall partitioning in a northern mixed forest canopy for soil water isotopic signatures in ecohydrological studies. Issue 2 (8th November 2019) - Snelgrove, Jenna R.; Buttle, J.M.; Tetzlaff, D.
Abstract: The forest canopy can play a significant role in modifying the amount and isotopic composition of water during its passage throughout the near‐surface critical zone. Here, partitioning of gross rainfall into interception, throughfall, and stemflow and its implications for the amount and isotopic composition of soil water was studied for red oak, eastern white pine, and eastern hemlock trees in a northern hardwood‐conifer forest in south central Ontario, Canada. Stemflow production was greatest for red oak as a result of its upward‐projecting branches and least for eastern white pine due to its horizontal branches and rougher bark. These stemflow contributions to the near‐bole soil surface failed to produce consistently wetter soils relative to distal locations from the bole for all tree species. There was also no consistent evidence of isotopic enrichment of throughfall and stemflow relative to gross rainfall or of stemflow relative to throughfall for red oak or eastern hemlock. However, there was isotopic enrichment of both throughfall and stemflow for eastern white pine with increasing maximum atmospheric vapour pressure deficit, which may reflect the potential for evaporative fractionation as a result of retention and detention of water moving through the canopy by the rougher bark of this species. Dry soil conditions limited sampling of mobile soil water during the study, and there was no consistent evidence that either throughfall or stemflow fluxes controlled temporal changes in the isotopic signature of soil water beneath the tree. Thus, the potential for throughfall and stemflow fluxes in northern hardwood‐conifer forests to modify the isotopic composition of water taken up by the tree via transpiration remains an open question. Abstract : Red oak converted more above‐canopy precipitation to stemflow compared with conifers such as eastern white pine, due to differences in branch architecture and bark roughness. Stemflow from eastern white pine was isotopically enriched relative to above‐canopy precipitation and throughfall. Near‐bole soil water isotopic signatures were generally unresponsive to stemflow inputs; nevertheless, such inputs may have implications for the isotopic composition of water taken up by the tree for transpiration.